EFFECT OF KARANJA BIODIESEL BLENDS ON THE CHARACTERISTICS OF DIESEL ENGINE - Sandeep YADAV; Amit KUMAR; Abhilasha CHAUDHARY (Scientific Journal of Silesian University of Technology. Series Transport, 2022)
Extensive research is being conducted to create and use a wide range of alternative fuels to accommodate the world's growing energy needs. The objective of this experimental investigation was to analyze the effects of Karanja biodiesel blends on the performance, combustion, and emission characteristics of a compression ignition (CI) engine vis-a-vis neat diesel. Important physical parameters of Karanja oil were examined experimentally after transesterification and determined to be within acceptable limits. BTE of Karanja biodiesel blends was about 3-8% lower than diesel. For Karanja biodiesel blends, BSFC was about 2-9% higher than diesel but exhaust gas temperature and volumetric efficiency were lower. Emissions characteristics such as nitrogen oxides, hydrocarbons, and carbon monoxide were also analyzed for various tested fuels. Karanja biodiesel blends resulted in lesser CO and HC formation. Nonetheless, NOx emissions were around 10% greater than diesel. Peak cylinder pressure, heat release rate, and maximum rate of pressure rise versus crank angle were among the combustion characteristics parameters considered in this study. Combustion analysis revealed that for Karanja biodiesel blends heat release rate and peak cylinder pressure were lower than for neat diesel. Findings indicate that Karanja biodiesel can be considered a viable diesel engine fuel.